The Nexus between Causal Macroeconomic Relations in Japan - Zestos, George K; Jiang, Yixiao; Simons, Hunter (Review of Economic Analysis)

(untitled) (International Centre for Economic Analysis, 2022)
Japan achieved phenomenal economic growth after WWII. Starting in the early 1990s, however, the Japanese economy began experiencing a prolonged deflation-stagnation period widely known as the “Lost Decades”. Based on data from the World Bank and the Federal Reserve Bank of Saint Louis, this paper employs an autoregressive distributed lags (ARDL) model to find evidence of a long run relation among the real GDP, real imports, the real exchange rate, and the public debt-to-GDP ratio for Japan. Once cointegration is established with the Bounds Test, Granger Causality tests are performed by employing an estimated Vector Autoregressive (VAR) model with the same variables. The empirical results support Granger causality in all directions. In particular, we found real imports and public debt-to-GDP ratio to directly cause real GDP. Interestingly, the real exchange rate causes real GDP indirectly via imports. The public debt had a negative effect on GDP but did not wreak havoc on the Japanese economy. The study also examines whether former Prime Minister Shinzō Abe’s unprecedented macroeconomic policies and structural reforms launched in 2013, known as Abenomics, are pulling Japan out of its economic doldrums.